2011
DOI: 10.2527/jas.2010-3357
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sex and castration on growth performance and carcass quality of crossbred pigs from 2 Large White sire lines1

Abstract: In total, 360 pigs slaughtered at 125 kg of BW and destined for the dry-cured industry were used to study the influence of sex and castration [immunocastrated males (IMC), surgically castrated males (CM), and intact females (IF)] in 2 terminal Large White sire lines [Top York (TY) and Tempo (TE)] on growth performance and carcass and meat quality. The female line was Large White × Landrace. The IMC pigs were immunized against gonadotropin-releasing factor (GnRF) with Improvac at 78 (experimental d 16) and 126 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
27
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 38 publications
(23 reference statements)
21
27
0
3
Order By: Relevance
“…This is in agreement with our previous study (Škrlep et al, 2010), whereas Gispert et al (2010) and Morales et al (2010) reported intermediate position of IC compared to SC and EM for IMF in semimembranosus and gluteus medius muscle, respectively. Studies comparing only IC and SC reported either no difference (Morales et al, 2011) or lower LD intramuscular fat in IC (Boler et al, 2011). If the deposition of IMF is related to other fat depots, such as leaf fat, LEA fat, and neck intermuscular fat, a similar pattern is observed, i.e.…”
Section: Meat Quality Traitsmentioning
confidence: 96%
See 1 more Smart Citation
“…This is in agreement with our previous study (Škrlep et al, 2010), whereas Gispert et al (2010) and Morales et al (2010) reported intermediate position of IC compared to SC and EM for IMF in semimembranosus and gluteus medius muscle, respectively. Studies comparing only IC and SC reported either no difference (Morales et al, 2011) or lower LD intramuscular fat in IC (Boler et al, 2011). If the deposition of IMF is related to other fat depots, such as leaf fat, LEA fat, and neck intermuscular fat, a similar pattern is observed, i.e.…”
Section: Meat Quality Traitsmentioning
confidence: 96%
“…There are not many studies dealing with the immunocastration effect on meat quality. They show for the most part the absence of any effect on pH 24 (Pauly et al, 2009;Gispert et al, 2010;Škrlep et al, 2010;Boler et al, 2011;Morales et al, 2011;), drip loss or colour (Pauly et al, 2009;Škrlep et al, 2010;Boler et al, 2011). On the other hand, some reports indicate IC to have darker meat than SC (Silveira et al, 2008), lighter than EM or lower drip loss than SC (Miclat-Sonaco et al, 2008).…”
Section: Meat Quality Traitsmentioning
confidence: 99%
“…These observations are in line with the studies conducted by Lundstrom et al, (2009) and Bonneau (1998) who indicated that the advantage of lean meat growth when shifting towards EM pigs may have decreased because of selection for leaner pig breeds. None of the studies on the interaction between genotype and castration method on carcass quality published thus far showed any significant interactions (D'Souza and Mullan, 2003;Morales et al, 2011 and. When shifting towards the production of immunocastrates or EM, it is relevant for the farmers to consider whether it is appropriate to continue with the current genetic line or whether it would be economically beneficial to change to lines characterised by a lower lean meat percentage and higher DG.…”
Section: Aluwé Tuyttens and Milletmentioning
confidence: 99%
“…Regarding the gender effect, barrows grew faster and had lower feed conversion ratio than gilts had been demonstrated by previous study (Morales et al, 2011). Meanwhile, Ellis et al (1996) reported that carcass yield was greater for gilts than castrates.…”
Section: Introductionmentioning
confidence: 77%